p53, p16 and Fhit Proteins Expressions in Chronic Esophagitis and Chagas Disease - Bellini, Marilanda Ferreira; Leite, Katia Ramos Moreira; Cury, Patricia Maluf; Silva, Ana Elizabete [UNESP] (Int Inst Anticancer Research, 2008)
Background: Models have suggested esophageal carcinogenesis can result front the alteration of sequences, leading to esophagitis, atrophy, dysplasia, carcinoma in situ and invasive carcinoma. While numerous genetic alterations have been reported in esophageal carcinogenesis, studies of benign lesions with precancerous potential are scarce. Materials and Methods: Immunohistochemistry was performed for p53, p16 and Fhit proteins in the esophageal mucosa from patients with Chagas disease (CD), chagasic megaesophagus (CM), chronic esophagitis (CE), esophageal squamous cell carcinoma (ESCC) and in normal mucosa (NM). Results: The proportion of p53-positive cases increased progressively according to the severity of the pathology CD (7.7%), CM (26.1%), CE (52.2%) and ESCC (100%). However, p16 and Fhit did not show any statistically significant differences among the groups. Conclusion: p53 overexpression is involved in the initial steps of esophageal carcinogenesis, supporting further evaluation of its utility as a marker in precursor lesions, conversely, losses of Fhit and p16 expression may not be significant.
Keywords: p53; p16; Fhit protein; esophagitis; Megaesophagus; esophageal carcinoma